Penanganan Longsor Pada Ruas Jalan Padang – Painan (Sta. 50+950 - 51+035) di Kabupaten Pesisir Selatan dengan Dinding Penahan Tanah dan Fondasi Tiang Bor - Laurency, Sonya Ostha; Andriani, Andriani; Hakam, Abdul; Istijono, Bambang (Jurnal Ilmiah Rekayasa Sipil, 2025)
High rainfall on steep slopes along the Padang – Painan city boundary road (Sta 50+950 – Sta 51+035) Pesisir Selatan Regency resulted in landslides and damage to retaining walls. This study aims to analyze slope stability, and retaining wall stability without and using bored pile foundations. The retaining wall used in this study is the Cantilever type. Slope stability analysis using the slices method was carried out by trial and error three times, the results showed a safety factor value (FS <1.25) which means the slope is unstable. The results of the slope improvement analysis using cantilever retaining wall without bored pile foundations showed that the structure was safe against overturning (FS = 3.9) and shear safety (FS = 2.3), but not safe against soil bearing capacity (FS = 1.5 <3). The addition of a single bored pile foundation to the retaining wall increased the bearing capacity to 3,443.43 kN but was unable to withstand the design load of 41,766.45 kN. Therefore, a pile group foundation with a maximum load capacity of 482,080.27 kN, and a permissible bearing capacity of 192,832 kN is used so that it can withstand the structural load. The estimated cost of geotechnical and structural work is Rp10,361,534,397.05 with an implementation time of 10 weeks. The results of this study provide technical recommendations for comprehensive slope and DPT repairs for similar conditions in the future.